Digital public relations strategy through social-media of the ministry of tourism and creative economy - Kesuma, Desmaria Puji (Jurnal Mantik, 2024)
The global Covid-19 pandemic, particularly impactful in Indonesia, has significantly affected tourism sector. On September 29 2022, the President of the Republic of Indonesia, Mr. Joko Widodo, issued directions to invite people to travel within the country. The aim of this research is to analyze the implementation of the four elements of the Ministry of Tourism and Creative Economy's strategic planning in the Proud to Travel in Indonesia Campaign using a model, and three digital public relations communication strategies through the Ministry of Tourism and Creative Economy's Instagram in the Proud to Travel in Indonesia Campaign. This research used a descriptive qualitative method by describing a phenomenon in detail and presenting the data found. This campaign was implemented with 4 (four) campaign strategy plans using Argenti theory (2013) and the implementation of 3 (three) digital public relations communication strategies using Cornelissen theory (2020). The results of the analysis carried out by the Ministry of Tourism and Creative Economy to support the national program, namely the Proud to Travel in Indonesia Campaign, are to create content related to government programs and government policies, created in a projected manner and also supported by re-branding. Messages on social media are informational, tour packages and travel fairs and the three types implementation of corporate communications strategy are information strategy and dialogue corporate strategy